Mindfulness-based interventions to reduce burnout and stress in physicians: a study protocol for a systematic review and meta-analysis - Johannes Caspar Fendel; Johannes Julian Bürkle; Anja Simone Göritz (BMJ Open)
Introduction Physicians often suffer from burnout and stress, not only affecting themselves, but also their patients and the healthcare system in general. An increasing number of studies suggest that mindfulness-based interventions improve physicians’ well-being as well as the quality of care they deliver. However, the evidence is scattered, and a systematic review and meta-analysis is lacking. To the best of our knowledge, this systematic review and meta-analysis will be the first to assess the effectiveness of mindfulness-based interventions in reducing burnout and stress among physicians. Further, it aims to uncover potential moderators of intervention effectiveness.Methods and analysis MEDLINE, Embase, PsycINFO, PSYINDEX, Web of Science, CINAHL and the Cochrane Central Register of Controlled Trials will be screened without language or publication date restrictions. In addition, backward and forward citation searches of included studies and relevant reviews will be conducted. Studies examining the effect of interventions for physicians explicitly based on mindfulness will be included. Primary outcomes will be pre-post changes in burnout and stress if assessed with validated measures. Two reviewers independently search, select and extract data, and rate the methodological quality of the studies. Both controlled and uncontrolled studies will be included. Randomised controlled trails will be meta-analysed separately using between-group effect. In addition, non-randomised trials including non-controlled before-after studies will be meta-analysed using within-group effect. Potential moderators and sources of between-study heterogeneity will be tested using meta-regression and subgroup analyses. Futhermore, a narrative synthesis will be pursued. The Grading of Recommendations Assessment, Development and Evaluation system (GRADE) will be used to assess the quality of the cumulated evidence.Ethics and dissemination Ethical approval is not required. Results will be published in a peer-reviewed journal and presented at international conferences.PROSPERO registration number CRD42019133077